Design And Development Of High Frequency High Power Transformer For Renewable Energy Application. - A. R., Abdul Razak; S., Taib; I., Daut (2005)
This paper presents a design and fabrication of a high frequency transformer for 5 kW power rating. Within an operating frequency of 25 kHz, a MnZn P type core has been utilized. Two set of E-E geometry cores had to be stacked in order to achieve rhe calculated 64.14 cm4 of the W^Ac volume. Test and validation of the designed shows that the prototype designed tansformer had proven to be very compact, higher fill factor, smaller in size, lighter in weight if compared to other winding approaches which utilizing copper round wires. The measured overall losses of the transformer itself were remain below the expected value of 32.974 W. The efficiency of the transformer was found to be at 93% average. Overall test results also show that the design and implementation of this high frequency power transformer is applicable especially fo renewable energy system..